Intraosseous Cavernous Hemangioma of Inferior Turbinate: A Rare Case Report - Akiner, M. N.; Akturk, M. T.; Demirtas, M.; Atmis, E. O. (Case Reports in Otolaryngology, 2011)
Objectives. To investigate hemangiomas in the differential diagnosis of the nasal cavity neoplasms, even though it is an extremely rare mesenchymal tumor of the nasal cavity, and the world literature was reviewed. Case Report. A 57-year-old woman applied to our department with a 5-year history of left-sided nasal obstruction without history of epistaxis, nasal packaging, or facial trauma. Anterior rhinoscopic examination revealed a mass originating from inferior turbinate that completely obstructs the left nasal cavity. Paranasal computed tomography (CT) showed that the bony mass originated from the anterior part of the left inferior turbinate. Surrounding tissues were normal, and there was not any erosion or destruction. Mass was excised by the endoscopic approach. Histological diagnosis was reported as osseous cavernous hemangioma. Conclusion. Hemangiomas are a rare cause of intranasal masses. Its unusual site and masked presentation makes the differential diagnosis difficult. When a bony hard, well-shaped mass was seen in the nasal cavity, the possibility of intraosseous hemangioma must be remembered.